COMPARISON ANALYSIS OF THE FACTORS INFLUENCING ACADEMIC ENTREPRENEURIAL BEHAVIOR AMONG THE STUDENTS OF SHAHID RAJAEE TEACHER TRAINING UNIVERSITY AND FARHANGIYAN UNIVERSITY OF TEHRAN: Life Sciences-Educational Management - N, TAHMASBIPOOR; A, TAHERI (International Journal of Life Science and Pharma Research, 2011)
This study aimed to analyze the factors which influence academic entrepreneurial among the students of Shahid Rajaee Teacher Training University and Farhangiyan University of Tehran. The study is a descriptive and applied research. The population included all students of Shahid Rajaee University and Tehran Farhangiyan University (N=6416). 400 students were selected through random cluster sampling. Linan and Chen (2009) questionnaire, Zhang and Bartel (2010) questionnaire, Wang, khow and souw (2009) questionnaire, and Knight, Helkam and Saympson (1994) questionnaire were used to collect the data. The results showed that all variables of this study (subjective norm, risk taking, self-efficacy, creativity and intrinsic motivation) have direct and significant effects on entrepreneurial purpose.